A Low-Loss Coaxial Cavity Microwave Bandpass Filter with Post-Manufacturing Tuning Capabilities - Zakaria, Z; Jawad, M. S; Othman, A. R; Gannapathy, V. R (2013)
This paper presents a low-loss coaxial cavity microwave bandpass filter with post-manufacturing tuning capabilities. A systematic filter development using a low-pass prototype as the starting point to produce a fourth-degree Chebyshev bandpass response is demonstrated. The coaxial cavity filter based on the transverse electromagnetic mode of the propagation has a center frequency of 2.5 GHz and a bandwidth of 160 MHz. An insertion loss (S21) of 0.15 dB and a return loss (S11) better than 15 dB are obtained, particularly in the passband. An excellent agreement between ideal circuit, EM simulation and measurement results has been achieved. The filter is then modified to have two channels, known as a diplexer, wherein center frequencies are at 2.5 GHz and 2.9 GHz at a bandwidth of 200 MHz. This type of microwave filter will be useful in any microwave system wherein low insertion loss and high selectivity are crucial, such as in base station, radar, and satellite transceivers.